Criminal Protection for Informers and Witnesses of Corruption Crimes in the Saudi Law - Ahmed Khalaf Atta Allah Al-Tuwairiqi; Mustafa Mohammed Bitar (International Journal of Law Research and Studies, 2025)
This study addresses the topic of "Criminal Protection for Informers and Witnesses of Corruption Crimes in the Saudi Legal System." It aims to analyze the effectiveness of the Saudi legal framework in providing adequate criminal protection for these individuals and to identify the challenges hindering the implementation of such protection, whether at the level of legal texts or practical application. To achieve this objective, the researcher adopted a descriptive and analytical methodology, relying on comparative analysis with leading international experiences such as the French and American legal systems, in addition to the normative framework established by the United Nations Convention against Corruption. The core problem of the study lies in the lack of sufficient protection for informers and witnesses of corruption crimes under the Saudi legal system, which makes them vulnerable to retaliation or professional discrimination. This deficiency leads to a weakening of general deterrence against corruption and diminishes the effectiveness of oversight measures within the Kingdom. The study concludes that the Saudi legal system has taken significant steps in this regard, particularly through the issuance of the Law on the Protection of Informers, Witnesses, Experts, and Victims, which represents a legislative milestone. However, challenges remain at the level of practical implementation, especially due to the lack of public legal awareness and the absence of an independent authority to manage protection programs, as is the case in some other countries.The study recommends strengthening the legal framework through clear implementing regulations and expanding the scope of protection to include all forms of harm that the informer or witness may face, whether professional, social, or psychological. It also calls for enhanced cooperation between regulatory and judicial authorities, the activation of psychological and legal support programs, and raising public awareness of individual rights and protection guarantees.
Keywords: Criminal Protection; Informers and Witnesses; Regulations; Saudi legal system; Comparative systems